Mixed Organometallic–Organic Hybrid Assemblies Based on the Diarsene Complex [Cp2Mo2(CO)4(μ, η2‐As2)], AgI Salts and N‐Donor Organic Molecules. Issue 15 (15th February 2021) - Elsayed Moussa, Mehdi; Shelyganov, Pavel A.; Seidl, Michael; Peresypkina, Eugenia; Berg, Nele; Gschwind, Ruth M.; Balázs, Gábor; Schiller, Jana; Scheer, Manfred
Abstract: The reaction of the organometallic diarsene complex [Cp2 Mo2 (CO)4 (η 2 ‐As2 )] (1 ) with Ag[Al{OC(CF3 )3 }4 ] (Ag[TEF]) yielded the Ag I monomer [Ag(η 2 ‐1 )3 ][TEF] (2 ). This compound exhibits dynamic behavior in solution, which allows directed selective synthesis of unprecedented organometallic–organic hybrid assemblies upon its reaction with N‐donor organic molecules by a stepwise pathway, which is supported by DFT calculations. Accordingly, the reaction of 2 with 2, 2′‐bipyrimidine (L1 ) yielded the dicationic molecular compound [{(η 2 ‐1 )2 Ag}2 (μ‐L1 )][TEF]2 (3 ) or the 1D polymer [{(η 2 ‐1 )Ag}(μ‐L1 )] n [TEF] n (4 ) depending on the ratio of the reactants. However, its reactions with the pyridine‐based linkers 4, 4′‐bipyridine (L2 ), 1, 2‐bis(4‐pyridyl)ethylene (L3 ) and 1, 2‐bis(4‐pyridyl)ethyne (L4 ) allowed the formation of the 2D polymers [{(η 2 ‐1 )Ag}2 (μ‐L x )3 ] n [TEF]2 n [L x =L2 (5 ), L3 (6 ), L4 (7 ), respectively]. Additionally, this concept was extended to step‐by‐step one‐pot reactions of 1, [Ag(CH3 CN)3 ][Al{OC(CF3 )2 (CCl3 )}4 ] ([Ag(CH3 CN)3 ][TEF Cl ]) and linkers L2 –L4 to produce the 2D polymers [{(η 2 ‐1 )Ag}2 (μ, L x )3 ] n [TEF Cl ]2 n [Lx =L2 (8 ), L3 (9 ), L4 (10 ), respectively]. Abstract : Hybrid coordination polymers : The Ag I monomer [Ag{[Cp2 Mo2 (CO)4 (η 2 ‐As2 )]}3 ][TEF] ([TEF]=[Al{OC(CF3 )3 }4 ]) was obtained by reaction of the organometallic diarsene complex [Cp2 Mo2 (CO)4 (η 2 ‐As2 )] with Ag[TEF]. In solution, this compound is in equilibrium with another monomeric species, [Ag{[Cp2 Mo2 (CO)4 (η 2 ‐As2 )]}2 ][TEF], exhibiting a less‐saturated Ag I center. This solution mixture reacts with a variety of ditopic pyridine‐based organic linkers to afford selectively 1D and 2D organometallic‐organic hybrid assemblies, including a helix‐like 1D structure.